1993
DOI: 10.1007/bf00365304
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of multiacetylated forms of histones by trichostatin A and its developmental consequences in early starfish embryos

Abstract: External application of 10 rig/ml (R)-trichostatin A (TSA), a potent and specific inhibitor of mammalian histone deacetylase, to the embryo of the starfish Asterina pectinifera inhibited development during the early gastrula stage before formation of mesenchyme cells. The TSA-sensitive period was limited to the mid-blastula stage before hatching. The pulse-chase experiment clearly demonstrated that TSA induced an accumulation of acetylated histone species in blastulae through inhibition of historic deacetylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…During the early development of A. pectinifera, the embryo undergoes extremely rapid cellular replication [16,18]. Slower rates of cell division characterize the embryo from the early to mid-blastula stages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During the early development of A. pectinifera, the embryo undergoes extremely rapid cellular replication [16,18]. Slower rates of cell division characterize the embryo from the early to mid-blastula stages.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the treatment of A. pectinifera embryos with trichostatin A, a potent and selective inhibitor of histone deacetylase [39], induces hyperacetylation of histone H4 and causes developmental arrest at the early gastrula stage [18]. Trichostatin A treatment causes suppression of the appearance of p28 in A. pectinifera embryos (T. Shimizu & S. Ikemagi, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…lnhibition of HD with trichostatin and/or trapoxin causes detransformation of sis-oncogene-transformed human cells (Yoshida and Sugita, 1992), induces differentiation of leukemic cells (Yoshida et al, 1985), arrests the cell cycle of rat fibroblasts in G, and G P (Yoshida and Beppu, 1988), and blocks starfish development at the early gastrula stage (Ikegami et al, 1993); in none of these systems does trichostatin or Aeo-containing cyclic peptides cause cell death.…”
Section: Discussionmentioning
confidence: 99%